Flood disaster mitigation modeling through participation community based on the land conversion and disaster resilience. Issue 8 (August 2022) - Nugraheni, Irma Lusi; Suyatna, Agus; Setiawan, Agus; Abdurrahman,
Abstract: The objective of this research is to determine the relationship between non-structural flood disaster mitigation models to reduce the impact of floods. The analysis is carried out on the basis of community participation, land conversion, and community resilience. The 1398 household was conducted at 2019 is used as the sample of this research. This research is focused on the mitigation modeling by adopting three models (CLEAR model, CLUE-S model, DROP model) as variables, 15 indicators and 65 sub-indicators. Three hypotheses were formulated to effectively carry out the research. Structural equation model is used to investigate the close relationship between the three models. The relation between CLEAR and CLUE-S models have a positive correlation is about 14.806, CLEAR and DROP models have a close relation is about 4598, and CLUE-S and DROP models have a close positive relation is about 4.004. The results of these three models are very valuable to the central and local governments for formulating the policies programs in designing sustainable non-structural flood mitigation and subsequent policies with references to the three models above which are effective to reduce the flood events. Abstract : Flood disaster; Mitigation modelling; Clear model; Clue-s model, Drop model.